Morphometric comparison of Characidae fish when n < p - Villegas Rivas, Danny (2020)
Currently, great importance has been given to the study of external morphology, especially in fish, when it is used as a means of identifying hybrids. This paper considers a LASSO model based on the truss protocol to compare morphological covarion patterns between specimens of Colossoma macropomum and the hybrid C. macropomum (♀) x P. orinoquensis (♂). In this study, 25 specimens of C. macropomum and 20 specimens of the hybrid C. macropomum (♀) x P. orinoquensis (♂), respectively, were analyzed. The method "Truss protocol" or "trusses" Strauss and Bookstein (1982) was used. LASSO model achieved to reduce the mean squared error. The final model obtained contains only seven covariates. LASSO model fitted on the morphological covariation patterns between specimens of C. macropomum and the hybrid C. macropomum (♀) x P. orinoquensis (♂) showed a good fit and allowed to correctly classify most of the specimens. Differences were observed in the area of the head and in the anterior part of the fish evidenced in covariates associated with hydrodynamic abilities and with foraging.